Information of the Sixth Conference of the Lithuanian Mathematical Society - Journal, Lithuanian Mathematical (Lithuanian Mathematical Journal, 1965)
Original title in Russian and Lithuanian: Информация о Шестом республиканском совещании Литовского математического общества Informacija apie šeštąjį respublikinį Lietuvos matematikų pasitarimą